Effects of urbanization on agricultural lands and river basins: Case study of Mersin (South of Turkey) - Duran, Celalettin; Gunek, Halil; Sandal, Ersin Kaya (Triveni Enterprises, 2012)
Largely, Turkey is a hilly and mountainous country. Many rivers rise from the mountains and flow into the seas surrounding the country. Mean while along fertile plains around the rivers and coastal floodplains of Turkey were densely populated than the other parts of the country. These characteristics show that there is a significant relationship between river basins and population or settlements. It is understood from this point of view, Mersin city and its vicinity (coastal floodplain and nearby river basins) show similar relationship. The city of Mersin was built on the southwest comer of Cukurova where Delicay and Efrenk creeks create narrow coastal floodplain. The plain has rich potential for agricultural practices with fertile alluvial soils and suitable climate. However, establishment of the port at the shore have increased commercial activity. Agricultural and commercial potential have attracted people to the area, and eventually has caused rapid spatial expansion of the city, and the urban sprawls over fertile agricultural lands along coastal floodplain and nearby river basins of the city. But unplanned, uncontrolled and illegal urbanization process has been causing degradation of agricultural areas and river basins, and also causing flooding in the city of Mersin and its vicinity. Especially in the basins, urbanization increases impervious surfaces throughout watersheds that increase erosion and runoff of surface water. In this study, the city of Mersin and its vicinity are examined in different ways, such as land use, urbanization, morphology and flows of the streams and given some directions for suitable urbanization.
Keywords: Urbanization; Land use; Degradation; Basins of river; Mersin